Association of tumor localization and treatment stage with anxiety and depression in patients with malignant tumors of the maxillofacial region - Oleksandr Belikov; Oleksandra Roshchuk; Nataliia Belikova; Ruslan Iakymenko; Yaroslav Karavan; Rauf Jafarov; Nataliia Lytovchenko; Liudmyla Belikova; Maksym Bernik; Roman Kostenko (Eurasian Journal of Medicine and Oncology, 2026)
Introduction: Despite advances in psycho-oncology, limited evidence is available regarding changes in the psychoemotional status of patients with malignant tumors of the maxillofacial region across different stages of treatment and rehabilitation, particularly in relation to tumor localization and the severity of functional and aesthetic impairments. Objective: This study aimed to evaluate the dynamics of anxiety and depression in patients with malignant tumors of the maxillofacial region at different stages of treatment and rehabilitation and to determine their association with tumor localization and the severity of anatomical, functional, and aesthetic impairments. Methods: A total of 85 patients with malignant tumors of the maxillofacial region were enrolled. Anxiety and depression were assessed using a modified Hospital Anxiety and Depression Scale (HADS), and an Integral Psychoemotional Index (IPEI) was calculated at hospitalization, during the preoperative period, and after surgery. Data were analyzed using appropriate statistical methods. Results: Anxiety, depression, and IPEI values progressively decreased throughout treatment, from 12.4, 10.8, and 2.31 at hospitalization to 6.7, 5.4, and 1.28 in the postoperative period, respectively (p < 0.01). Tumor localization was significantly associated with psychoemotional status. The highest IPEI values were observed in patients with tumors of the nasal cavity and maxillary sinus, whereas the lowest values were recorded in patients with hard and soft palate tumors (p < 0.01). Anxiety and depression levels were significantly higher in women and younger patients. Conclusion: Patients with malignant tumors of the maxillofacial region demonstrated progressively lower anxiety and depression levels during treatment and rehabilitation. Psychoemotional disturbances were associated with tumor localization, with the highest burden observed in patients with tumors affecting the nasal cavity and maxillary sinus.